Prueba de concepto mediante el desarrollo de una APP Android para la búsqueda de repuestos de vehículos en dispositivos móviles (2021)
Databases and mobile applications have been having a great boom within companies today. This is why it could be said that 95% of workers have a smartphone in their possession, and it is here where industries without investing in these devices use them seeking to automate and streamline processes within their facilities, generating greater profits and saving means. The purpose of this project is to combine these two tools and streamline a search process for spare parts for mobile vehicles in an application for smartphones with Android operating system, users will have the opportunity to have a large amount of information on their mobile phones. quick and easy way as well as the option to find a spare part and see important information about it.